Effect of Temperature on Thermal Resistance of Salmonella Typhimurium in Simulated Wheat Gluten-Based Patty - Ng, Hui Lin; Ahmad, Nurul Hawa (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Wheat gluten-based patty, known as ‘seitan’, is used for alternative meat products. However, repeated Salmonella outbreaks linked to flour raise concerns; therefore, this study aimed to assess the effect of temperature on the thermal resistance of Salmonella Typhimurium in simulated wheat gluten-based patty at 60℃, 65℃ and 70℃. A mixture of water (100 mL), wheat gluten flour (75 g), canola oil (10 mL) and salt (1 g) were inoculated with Salmonella inoculum (1 mL). Samples (5 g each) were packed, flattened, and vacuum sealed in a double bag subjected to heat treatment before two subsamples were pulled at pre-determined time intervals for Salmonella survivor enumeration. A linear relationship between log reduction and heat treatment time was observed at all temperatures, indicated by Root Mean Square Error (RMSE), which was < 1.3. The D values were estimated using the USDA Integrated Pathogen Modelling Program (IPMP), and yielded 5.86, 3.34, and 2.00 min for 60℃, 65℃, and 70℃, respectively. The calculated z value was 12.4℃. Both D and z values obtained in this study were higher than the meat patty reported in the literature, suggesting the need for further investigations to design more effective thermal control to inactivate Salmonella in wheat gluten-based patty.